WHAT CAN THE ELEMENTARY SCHOOL CONTRIBUTE IN A CONTINUOUS SCIENCE PROGRAM?. - Croxton, W. C. (Science Education, 1939)
The article focuses on the contribution of elementary schools in teaching science in the higher levels of the educational system in the U.S. In 1912, the introduction of teaching science in the elementary level has begun particularly in the ninth grade. However, the entry of science in the ninth grade curricula has raised questions and confusions among the teachers, educators and to the pupils as well. Its introduction into the earlier years is causing teachers to question the suitability and grade placement of the work that is being done at all levels while pupils are confused on the difference of seventh, eighth and ninth-grade science. When estimating the possible outcomes of elementary science, its contribution to learnings is not the primary purpose rather, it is credited in terms of avenues of interest and satisfaction opened, scientific and social attitudes developed, outlooks changed through concepts comprehended and abilities developed to do useful things.